Customer-centric strategy driving innovativeness and business growth in international markets - Tuominen, Sasu; Reijonen, Helen; Nagy, Gábor; Buratti, Andrea; Laukkanen, Tommi (International marketing review, 2023)
PurposeThe motivation for this study comes from decision making related to strategic marketing orientations in international markets. The authors examine if customer orientation and customer relationship orientation perform as two distinct constructs in driving firm innovativeness, and how together they support business growth among export firms. This study aims to suggest a customer-centric strategy for export firms that drive innovativeness and growth.Design/methodology/approachAn international corporation specialized in company information services provided a list of the contact information of Italian companies. The authors sent an email request to respond to an online survey and received 416 effective responses from firms operating in export markets. The authors propose and empirically test a model in which customer orientation, customer relationship orientation and innovativeness predict business growth. This model controls for the effects of firm size, industry and customer type (B2B vs. B2C).FindingsThe study findings suggest that customer orientation and customer relationship orientation are two distinct strategic orientations driving innovativeness. However, they do not directly affect business growth. Instead, they require the innovativeness of an exporter to materialize as business growth.Practical implicationsThe results of the study recommend business strategies focusing not only on customer needs and satisfaction but also on retaining current customers and building customer relationships in international markets. Firms can learn from international customers and develop effective customer-centric strategies to spread the acquired information into the internal decision-making as it contributes to firm innovativeness and business growth in international markets.Originality/valueThis study is one of the pioneering studies combining customer orientation and customer relationship orientation, showing their theoretical and empirical divergence. This study is also among the first which tests how the two strategic orientations together with innovativeness promote business growth among export firms. The authors add understanding of the synergistic effects both of using customer information and developing deeper relationships on firm innovativeness and performance among exporters.